Jejunal gastrointestinal stromal tumour masquerading as an ovarian cancer: A case report - Sohail, Mushtaq; Richelle, Chua; Sze Kiat, Sim; Nik Azim, Nik Abdullah (Malaysia Medical Association, 2022)
A 60-year-old lady presented with lower abdominal discomfort and a huge palpable intra-abdominal mass for 4 months, with significant weight loss over half a year. Transvaginal ultrasonography and computed tomography (CT) abdomen showed a large right solid cystic mass likely ovarian in origin. The CA-125 was raised. With the provisional diagnosis of ovarian cancer patient underwent laparotomy at Hospital Umum Sarawak, Malaysia. However intraoperative findings showed that uterus and both ovaries were normal. The tumour was arising from the jejunum and adherent to the dome of the urinary bladder and right broad ligament. The tumour was resected and final diagnosis was jejunal gastrointestinal stromal tumour (GIST). We described this case which was misinterpreted as an ovarian cancer.